Bagenen-Botolan as Basic Concepts Formation of Settlement in Dieng Mountains - Heri Hermanto; Adinda Septi Hendriani (Tesa Arsitektur, 2018)
Settlements in the Dieng Mountains is a manifestation of the culture of Dieng society. On a micro scale, bagenen connected by botolan is a settlement element that is always present in the Dieng community house. Bagenen-botolan becomes the main container of social, cultural and economic activity. When the settlements develop, the community then uses latar ombo for social, cultural, economic and sport activities that cannot be done in Bagenen-botolan. Between latar ombo one with the other is always connected by jalan latar and jalan tritian. This phenomenon raises the notion that, in the village scale, latar ombo that connected jalan latar and jalan tritian became a kind of bagenen-botolan. The notion is further strengthened by the existence of a village field that is always connected by jalan terabasan. Research questions that are then proposed are; what is the concept underlies the formation of settlements in the Dieng Mountains.The results of grandtour and minitour found 8 (eight) themes, namely, 1) The kinship system as a village builders, 2) Bagenen as a multifunctional space, 3) Latar ombo as bagenen in village scale, 4) Field as multifunctional space on the scale between villages, 5) Bagenen connected botolan 6) Latar ombo connected by jalan latar and jalan tritian, 7) The mosque connected by jalan latar and jalan tritian, 8) The field connected by jalan terabasan on the scale between villages.Inductive analysis of the eight themes found three concepts underlying the formation of settlements in the Dieng Mountains, namely: 1) Connected concepts, 2) Nyepetno concept, and 3) Brayan concept.The concept is empirically seen on all space scales. Layout arrangement of physical elements of settlement in Dieng Mountains always refers to this concept. These findings are a significant contribution for the science of architecture especially related to the spatial and values that form the Mountains settlements.